UPAYA INTERNATIONAL CENTRE FOR SETTLEMENT OF INVESTMENT DISPUTES (ICSID) DALAM PENYELESAIAN SENGKETA PERDAGANGAN ROKOK (STUDI KASUS URUGUAY DAN PHILIP MORRIS) - M Iqbal Sidiq; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses ICSID's efforts to resolve the cigarette trade dispute between Uruguay and Philip Morris. Philip Morris sued Uruguay to ICSID with violations committed by Uruguay in the form of its government policies, namely Regulation 80/80 and Ordinance 514.This study uses descriptive method with a qualitative approach which emphasizes the disclosure strategy made by PT. Glico Wings in marketing ice cream in Indonesia. Research data obtained from books, journals, official documents and websites that support the author's hypothesis. The author uses the perspective of liberalism and the level of analysis of multinational corporations (MNCs) according to Patric Morgan. And the theory used in this research is the theory of competitive advantage (Competitive Advantage) by Michael Porter. According to Porter, strategy allows organizations to gain a competitive advantage from three bases: cost leadership, differentiation and focus. The results showed that the tribunal results from ICSID were in favor of Uruguay and required Philip Morris to drop all charges and pay a fine of USD 7 million. Keywords: Liberalism, The Role of International Organizations, Trade Disputes